Disaster Mitigation Training for Disaster Preparedness Groups in Batang Arau Village, South Padang Sub-District, Padang City - Trisfa Augia; Muhammad Ilham Basgoro; Muhammad Agung Satriya; Nabilla Putri Amanda; Nur Fatia; Dalilla Ziva Maharani; Rahmi Martfida; Mufidah Rona; Lathifah Mahirah; Ufi Chaerani; Vania Nabila Ferdin; Cindy Amalia Pulungan; Nabiha Zaafarani; Afadhil Arnandes Putra; Intan Puspita Sari; Syahlan Alif Pratama Jusri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Indonesia is a disaster-prone region because it is located in the Ring of Fire and at the confluence of four tectonic plate faults: the Eurasian, Indo-Australian, Philippine Sea, and Pacific plates. A disaster is an event that cannot be predicted in terms of its arrival and impact but can be reduced in terms of risk. Community preparedness related to disasters needs to be improved because of the risk of disasters that can threaten the lives and livelihoods of people affected by disasters. Padang City is one of the coastal areas in West Sumatra Province with the risk of disasters such as earthquakes, tsunamis, and landslides because one of the factors is its geographical condition, which is located in a potential natural disaster area. Therefore, preparedness training is needed to help people who live in disaster-prone areas cope with and reduce disaster risks. This disaster preparedness and mitigation training was held on 8 November 2023 at the Batang Arau Village Office, Padang Selatan District, Padang City. The conclusion obtained after the implementation of this activity is the community's insight into the importance of being prepared and mitigating disasters that have the potential to occur in residential areas.